An ultra-compact deterministic source of maximally entangled photon pairs - M. Langer; P. Ruchka; A. Rahimi; S. Jakovljevic; Y. G. Zena; S. A. Dhurjati; A. Danilov; M. Pal; R. Bassoli; F. H. P. Fitzek; O. G. Schmidt; H. Giessen; et al. (APL Photonics, 2025)
We demonstrate an ultra-compact source of on-demand, maximally entangled photon pairs using single GaAs quantum dots embedded in monolithic microlenses coupled to a lensed single-mode fiber. A 3D-printed micro-objective with a numerical aperture of 0.6 enables efficient fiber coupling and near-diffraction-limited performance with 604(16)  nm resolution directly in the cryogenic environment at 3.8 K. The system achieves high single-photon emission rates [392(20)  kHz] and purities [99.2(5)%] using two-photon resonant excitation. Leveraging the exciton–biexciton cascade, it produces near-maximally entangled photon pairs with peak entanglement negativities of 2n = 0.96 ± 0.02. The presented quantum light source combines state-of-the-art performance and long-term stability with a dramatically reduced system footprint, making it well-suited for seamless industrial integration.